RAFT synthesis of cellulose‐g‐polymethylmethacrylate copolymer in an ionic liquid. Issue 6 (11th June 2012) - Lin, Chunxiang; Zhan, Huaiyu; Liu, Minghua; Habibi, Youssef; Fu, Shiyu; Lucia, Lucian A.
Abstract We demonstrate for the first time the feasibility in conducting the graft copolymerization of methylmethacrylate (MMA) with cellulose by the means of the reversible addition‐fragmentation chain transfer (RAFT) polymerization in an ionic liquid [1‐N‐butyl‐3‐methylimidazolium chloride] (BMIMCl). Cellulose was first converted to a macromolecular chain transfer agent to which MMA was grafted by RAFT in BMIMCl. The success of the occurrence of different reactions was validated by elemental analyses, Fourier transform infrared and nuclear magnetic resonance spectroscopies. The results demonstrate that the MMA polymer chains were grafted onto the cellulose while the use of the ionic liquid as a reaction medium enhanced the polymerization rate to a moderate extent. Gel permeation chromatography analysis of poly(MMA) chains cleaved from the cellulose by acidic hydrolysis indicated low polydispersity indices (ca. 1.3) that were consistent with the "living" nature of the RAFT. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013